Property is only another name for monopoly - E. A. Posner; E. G. Weyl (Russian Journal of Economics and Law, 2018)
Objective: to consider the possibility of a property tax promoting allocative efficiency without losses to investment efficiency. Methods: dialectical approach to the cognition of social phenomena, enabling to analyze them in their historical development and functioning in the context of a set of objective and subjective factors, which determined the choice of the following research methods: formal-logical, comparative-legal, sociological.Results: the existing system of private property interferes with allocative efficiency by giving owners the power to hold out for excessive prices. The authors propose a remedy in the form of a tax on property, based on the value self-assessed by its owner at intervals, along with a requirement that the owner sell the property to any third party willing to pay a price equal to the self-assessed value. The tax rate would reflect a tradeoff between gains from allocative efficiency and losses to investment efficiency, likely in the range of 5 to 10 percent annually for most assets. The detailed design of this system is discussed from an economic and legal perspective. Scientific novelty: the author proposes a paradigm of new economy relying not on the private property institution, but on the partial property with Harberger taxation system. Practical significance: the authors view practical examples of Harberger taxation implementation for various property types and objects. It is shown that the global trends towards economy digitalization, in particular, the Internet of Things (IoT), the blockchains, the electronic auctions and geo-positioning of the property objects are the key technologies for practical implementation of Harberger taxation system.